New Specimens of Platyrrhine Primates from Patagonia (Pinturas Formation, Early Miocene) - Novo, Nelson Martin (2015)
Here we report nine new fossil specimens of platyrrhine primates collected in late Early Miocene deposits of the Pinturas Formation, Argentine Patagonia, during two joint paleontological expeditions in 2004 and 2013 carried out by the Centro Nacional Patagónico (CENPAT, Puerto Madryn, Argentina), Stony Brook University, and Laboratorio de Investigaciones en Evolución y Biodiversidad (LIEB, Universidad Nacional de la Patagonia “San Juan Bosco”, Sede Esquel, Argentina).